In-Depth Partial Discharge Inception Voltage Analysis in Laminated Busbar by Means of Experimentations and Simulations - Oussama Abdel Illah Rahmouni; Sonia Ait-Amar; Stephane Duchesne; Jean-Francois Wecxsteen (IEEE Access)
Laminated Busbars (LBBs) have emerged as the most effective solution for high power electronic devices, offering low parasitic inductance and remarkable current capabilities. However, the design of LBB presents challenges related to criteria such as the busbar’s parasitic inductance and Partial Discharge Inception Voltage (PDIV). As power converter devices evolve, the balance between these two factors becomes increasingly complex, as increasing PDIV through thicker insulation alone also leads to higher parasitic inductance. This paper aims to address this issue by introducing a comprehensive model that correlates the PDIV of the LBBs with various parameters, including geometric aspects and dielectric material properties. A probabilistic approach is also used in order to study the Partial Discharge (PD) occurrence. The model is incorporated into an efficient software package, empowering LBB manufacturers to achieve more streamlined designs that meet PDIV requirements while adhering to other constraints. Moreover, practical tests have been carried out to validate the model with varying temperatures and pressures. It was found that the experimental PDIV values for the LBB samples drop by 19% between 30°C and 200°C at ground level and by 51.4% between 1 bar and 0.145 bar at 30°C. It was also found that the model based on Paschen’s criteria is capable of accurately predicting PDIV in LBB samples as a function of both temperature as well as pressure. It was only off by around 5.9%.